Mediocracia y pandemia: los diarios metropolitanos y el poder político en cuarentena (Monográfico) - Fontana, Walter (2023)
The work develops the phenomenon of mediocracy through the Intermedia Agenda of the most representative graphic media of the Autonomous City of Buenos Aires (Clarín, La Nación, Página/12, Crónica and Diario Popular).The objective of the study is to analyze the relationship between the ruling elite and the media for the imposition of themes through the front pages of newspapers during the first period of the pandemic, considering the reading contract relevant to each newspaper. The importance of the topic and its justification are based on the opportunity to analyze the relationship between two members of Political Communication - the media and the ruling elite - through the Media Agenda in times of health crisis. The research has its center of gravity in the Agenda Setting Theory, starting from what to think - First Level of Agenda Setting - through the media agenda of the graphic media. What stands out is the coincidence of interests between political power and the media as actors of Political Communication to present an issue to be debated in society, as long as it is a threat to the system. In this way, the effects of the Media Agenda on citizenship emphasize the situation when an event is directly experienced (obstrusive issues).The relationship between the ruling Elites and the media that are shown are not only presented as generators of consensus, but also as legitimizers of political actions.